Components of self-evaluation of young learners at primary school - Vulin Milijana R. (University of Kragujevac - Faculty of Pedagogy, Užice, 2022)
Student self-evaluation is a phenomenon that increasingly occupies the thoughts and interests of both educational workers and society as a whole. This is due to the fact that the educational process has lost its characteristics of evaluation and assessment in well-known didactic relations where teachers are the only evaluators and students are the exclusive objects in the implementation of that process. Relying on the modest results of previous studies and research of studentself-evaluation, empirical research was prepared and conducted with the aim of determining the connection between the components of self-evaluation of young learners at primary school. The research included 208 young learners at primary school. The method of theoretical analysis and synthesis, the research method as well as the analytical-descriptive method were applied in the interpretation of the obtained results. Based on the obtained results, it was found that students assessed the representation of individual components of self-evaluation as fairly equally represented (M = 3.90) and a statistically significant correlation was found among the assessed components of self-evaluation of young learners at primary school. The results of the research imply the need to introduce not only student self-evaluation into teaching practice with the aim of improving student success, but also the democratization of relations in teaching, which raises various questions for further scientific research.